1994
DOI: 10.1159/000188022
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Eliminates the Attenuating Effect of Castration on the Progressive Glomerular Injury in Hypercholesterolemic Male Imai Rats

Abstract: Hypercholesterolemic Imai rats, especially males, spontaneously develop proteinuria and glomerulosclerosis. We have shown that castration attenuated the progression of glomerular injury in male Imai rats. The present study was designed to investigate whether the attenuating effect of castration on glomerulosclerosis is eliminated by administration of testosterone. Testosterone propionate (TP) eliminated the attenuating effect of castration on the progression of glomerular injury by significantly and dose depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Sex hormones may also be involved in the different evolution of renal function between males and females in response to the prolonged HPI. In support of this hypothesis, it has been shown that castration of male rats seems to have a beneficial effect on the development of glomerulosclerosis, whereas treatment with testosterone accelerates the disease (23). It has also been shown that estrogens reduce glomerulosclerosis susceptibility (19).…”
Section: Discussionmentioning
confidence: 94%
“…Sex hormones may also be involved in the different evolution of renal function between males and females in response to the prolonged HPI. In support of this hypothesis, it has been shown that castration of male rats seems to have a beneficial effect on the development of glomerulosclerosis, whereas treatment with testosterone accelerates the disease (23). It has also been shown that estrogens reduce glomerulosclerosis susceptibility (19).…”
Section: Discussionmentioning
confidence: 94%
“…This hypercholesterolemic Imai rat, derived from Sprague-Dawley rats, has a markedly elevated rate of urinary protein excretion, especially in males [1, 2, 3, 4]. Because of this higher susceptibility of male Imai rats to focal and segmental glomerulosclerosis, we previously studied the effects of sex hormones on the development of glomerular injury both in male and in female Imai rats [4, 5, 6, 7]. We found that estrogen replacement therapy does not eliminate the aggravating effect of ovariectomy on glomerular injury and rather aggravates it [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other in vitro studies demonstrated that estrogen inhibits procollagen type III and increases the production of collagenase (11)(12)(13). Furthermore, castration of male rats seems to have a beneficial effect on the development of glomerulosclerosis (14), whereas treatment with testosterone accelerates the disease (15). Recent studies demonstrated that glomerulosclerosis susceptibility is associated with diminished estrogen receptor expression in mesangial cells (16).…”
mentioning
confidence: 99%